PENGARUH PENGUNGKAPAN BIAYA LINGKUNGAN SESUAI PSAK 33 DAN PERATURAN PEMERINTAH NOMOR 78 TAHUN 2010 TERHADAP KINERJA KEUANGAN - Jamingatun Hasanah; Mediya Destalia (Politeknik Negeri Batam, 2017)
This study aims to examine the effect of disclosure of environmental costs according to IAS 33 and Government Regulation No. 78 of 2010 again shows the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX). There are four independent variables in this study, the disclosure of the costs of stripping activity, environmental management activities due to production, environmental management activities due to exploration and evaluation, and reclamation of closure, and the dependent variable is Return On Investment. The sample used in this study. The total sample of this research is 12 companies. The existing data were analyzed by using multiple linear regression with panel data approach using Eviews 9. The result of hypothesis testing showed that there was significant significant influence between stripping activity and environmental management activity due to production to financial performance (Return On Investment). There is no influence between environmental management activities due to exploration and evaluation, and the closure of reclamation to financial performance (Return On Investment). F-test results revealed that the expenditure of stripping activity (X1), environmental management activities due to production (X2), environmental management activities due to exploration and evaluation (X3), and reclamation closure (X4) simultaneously have a significant effect on Return On Investment.